(untitled) (ASEAN Engineering Journal, 2025)
Papaya peel is a fruit waste that was usually dumped into the environment. One way to utilize papaya peel waste was to convert it into a fermented product like bacterial cellulose. In this study, the effect of various bacterial cellulose nitrogen sources such as bean sprouts, coconut milk and urea food grade were used to produce bacterial cellulose from papaya peel. In addition, the determination of the bacterial cellulose kinetic parameters and techno-economic analysis were also evaluated. The results from this research showed that urea food grade as nitrogen source produced highest bacterial cellulose. Longer fermentation time produced higher bacterial cellulose and lower water content in bacterial cellulose production. From kinetic model optimization with bacterial cellulose data, kinetic parameters such as maximum specific growth rate (µmax), monod constant (Ks), cell death rate constant (Kd), and cell maintenance constant (m) were 0.06 (day-1), 1.25 (g/L), 0.117 (day-1), and 0.568 (day-1). Techno-economic evaluation showed that bacterial cellulose production with recycle medium stage produced high profitability. Profitability parameters value such as return of investment (ROI), payback period (PBP), net present value (NPV), and internal rate of return (IRR) were 75.92%, 1.01 years, US 1,839,257,209, and 76.94%. This research showed that higher bacterial cellulose yield can be produced from papaya peel waste and urea food grade. Techno-economic simulations showed that large-scale production of bacterial cellulose from papaya peel waste can be profitable by recycle the fermentation medium.